Puasa Sebagai Ibadah Universal: Studi Komparatif Al-Quran dan Tradisi Puasa Sebelum Islam - Mely Bilqisti Aula; Salwa Eka Novita Fitri; Widodo Hami (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
Fasting is a form of worship known in various major world religions, such as Islam, Judaism, Christianity, Hinduism and Buddhism. In Islam, fasting is not only interpreted as refraining from eating, drinking and sexual relations, but also includes controlling negative speech, hearing, views and thoughts. QS. Al-Baqarah verse 183 emphasizes the obligation of fasting for Muslims as part of a universal tradition that is also known to followers of previous heavenly religions. This article aims to explore the fasting tradition in religions other than Islam and analyze the similarities, differences and continuity of religious values ​​from the perspective of the Koran. This research uses qualitative methods with a comparative study approach to the Al-Qur'an, analyzing the QS. Al-Baqarah: 183, tafsir, as well as other religious and cultural literature. The research results show that although there are differences in the form of fasting practice, the main goals are often similar, namely drawing closer to God, cleansing the soul, and strengthening social solidarity. This emphasizes the universality of the value of fasting in various religious traditions. Keywords: Fasting, Religious Traditions, Q.S. Al-Baqarah verse 183, Universal